Health Education Specialists' Knowledge, Attitudes, and Perceptions of the Patient Protection and Affordable Care Act. Issue 2 (March 2016) - Strong, Jessica; Hanson, Carl L.; Magnusson, Brianna; Neiger, Brad
The changing landscape of health care as a result of the Patient Protection and Affordable Care Act (ACA) may provide new opportunities for health education specialists (HES). The purpose of this study was to survey HES in the United States on their knowledge and attitudes of the ACA and assess their perceptions of job growth under the law. A random sample of 220 (36% response rate) certified HES completed a 53-item cross sectional survey administered online through Qualtrics. Findings were compared to public opinion on health care reform. HES are highly favorable of the law (70%) compared to the general public (23%). A total of 85% of respondents were able to list a provision of the ACA, and most (81%) thought the ACA would be successful at increasing insured Americans. Over half (64.6%) believe job opportunities will increase. Those who viewed the law favorably were significantly more likely to score better on a knowledge scale related to the ACA. HES understand publicized provisions but are uncertain about common myths and specific provisions related to Title IV, "Prevention of Chronic Disease and Improving Public Health." Directed and continuing education to HES regarding the ACA is warranted.